An Examination of Women in Federal Law Enforcement: An Exploratory Analysis of the Challenges They Face in the Work Environment. (July 2015) - Yu, Helen H.
For a study of occupational barriers, qualitative and quantitative data were generated from surveys collected from 168 women working in 34 federal law enforcement agencies and varying in race, ethnicity, age, rank, and tenure. All women report at least one occupational barrier in the workplace. Pervasive negative attitudes from male colleagues, lack of high-ranking female role models, and work–life balance issues prove to be the biggest barriers women face in federal law enforcement. Despite the obstacles, women not only persist against the challenges but also highlight the unique attributes of federal law enforcement to the policing research community.